Probing Active Sites and Reaction Intermediates of Electrocatalysis Through Confocal Near-Infrared Photoluminescence Spectroscopy: A Perspective - Chakrapani, Vidhya (Frontiers in Chemistry, 2020)
Electrocatalytic reactions such as oxygen evolution (OER) and oxygen reduction reactions (ORR) are one of the most complex heterogeneous charge transfer processes because of the involvement of multiple proton-coupled-electron transfer steps over a narrow potential range and the formation/breaking of oxygen-oxygen bonds. Obtaining a clear mechanistic picture of these reactions on some highly active strongly-correlated oxides such as MnOx, NiOx, and IrOx has been challenging due to the inherent limitations of the common spectroscopic tools used for probing the reactive intermediates and active sites. This perspective article briefly summarizes some of the key challenges encountered in such probes and describes some of unique advantages of confocal near-infrared photoluminescence (NIR-PL) technique for probing surface and bulk metal cation states under in-situ and ex-situ electrochemical polarization studies. Use of this technique opens up a new avenue for studying changes in the electronic structure of metal oxides occurring as a result of perturbation of defect equilibria, which is crucial in a broad range of heterogeneous systems such as catalysis, photocatalysis, mineral redox chemistry and batteries.